Exploring the impact of iron production on forest and woodland resources: estimating fuel consumption from slag. Issue 2 (16th December 2019) - Iles, Louise
ABSTRACT: Reconstructing past anthropogenic influences on forest and woodland resources is an important tool to understand the development of present patterns of land use, and their long-term impacts. Past metallurgical activity undoubtedly consumed significant charcoal, exploiting forest resources for fuel at various stages of metal extraction and processing. This study aimed to quantify this fuel consumption from archaeometallurgical remains, with North Pare as a case study – a prominent centre of precolonial iron production activity in north Tanzania, and a mountainous region subject to considerable erosion processes attributed to changes in forest cover. Archaeometallurgical remains from Pare were examined with bulk chemical analysis, optical microscopy and elemental analysis to reconstruct Pare's past iron production technologies. The data was interrogated to distinguish the contribution of the fuel ash to the smelting system, with implications for our understanding of past forest degradation processes in relation to metallurgy, reducing reliance on potentially problematic analogy.